As práticas de relações públicas na cultura digital : uma análise da narrativa transmídia do Magazine Luiza através da personagem Lú - Silva, Claudia Palma da (2015)
This dissertation is a study into the use of transmedia storytelling as practiced in Public Relations, analyzing the content produced by "Magazine Luiza" through the character of "Lu". Through content analysis and case studies, one observes how the story of the character flows between various kinds of digital media, and how this strategy of communication can be associated to Public Relations practices. The concept of transmedia storytelling establishes what Jenkins (2009) defines as a story which develops through multiple media platforms, with every new piece of context contributing in its own distinct and valuable ways to the whole. Analyzed mediums included the brand's website and blog, Facebook, Google+, Twitter, and Youtube.